2018
DOI: 10.3389/fneur.2018.00661
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of an Anti-NMDA Receptor Autoantibody Diagnostic Bioassay

Abstract: Anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis is one of the most frequently encountered autoimmune encephalitis. The pathogenesis of both anti-NMDAR encephalitis and schizophrenia involve down-regulation of NMDA receptors. Whether autoantibody-mediated destruction of neuronal NMDA receptors is associated with schizophrenia or first-episode psychosis (FEP) remains unclear, as the current findings from different groups are inconsistent. The main culprits are likely due to heterogeneity of autoanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…It is well-known that the antibody of AE can remain unknown in up to 40-50% of cases [6,7]. Moreover, the false-negative result of anti-NMDA IgG antibodies, including CSF with commercial laboratory kit testing, has led to new laboratory techniques to improve the sensitivity of antibody testing [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…It is well-known that the antibody of AE can remain unknown in up to 40-50% of cases [6,7]. Moreover, the false-negative result of anti-NMDA IgG antibodies, including CSF with commercial laboratory kit testing, has led to new laboratory techniques to improve the sensitivity of antibody testing [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The only symptom was partial seizures in the right limb [11]. False positiveness of anti-NMDAR antibody in both serum and CSF was also reported in Lyme disease [12], False positiveness in serum has been found in multiple sclerosis [13], Creutzfeldt-Jakob disease [14], and schizophrenia [15].Therefore, besides autoantibodies detection, careful clinical observation is also warranted. False negative result is also possible.…”
Section: Discussionmentioning
confidence: 99%
“…Nan-Chang Chiu and his colleges found that replacing reporter fluorophore fluorescein isothiocyanate in the commercial kits with Alexa Fluor 488 could obtain better detection result, especially in samples with low titers (18) because the fluorescence from Alexa Fluor 488 was brighter and more stable (55,56). A more sophisticated optic/imaging device is recommended because it allows even weak signals to be displayed from samples with low titers.…”
Section: Optimization Of Detection Assays In Practicementioning
confidence: 99%
“…Some anti-NMDAR encephalitis patients could be misdiagnosed as mentally ill and missed early effective immunosuppressive therapy if they showed isolated psychiatric episodes in the early days. However, once these misdiagnosed patients received the individualized immunotherapy (first-line immunotherapy including corticosteroids, intravenous immunoglobulins or plasma exchange; or second-line immunotherapy such as rituximab or cyclophosphamide, or both, or long-term immunotherapy (mycophenolate mofetil or azathioprine >1 year), their symptoms could be gradually cured (18). Thus, improving the sensitivity and specificity of autoantibody diagnostic bioassay in NMDAR antibodies is meaningful.…”
Section: Introductionmentioning
confidence: 99%